Analysing and designing visualizations – Diagrammatics (1984) revisited - Richards, Clive; Engelhardt, Yuri (InfoDesign, 2022)
This paper reviews how the authors’ current framework – the DNA of visualization – has evolved from the work laid out in Diagrammatics (Richards, 1984). The goal of this line of work was, and is, to enable the analysis and specification of an extensive range of different types of visual representations of information, such as statistical charts, maps, family trees, Venn diagrams, flow charts, texts using indenting, technical drawings and scientific illustrations. Inspired by an analogy with language, fundamental possibilities of graphic organization were identified in 1984. This work has been further developed into the current DNA of visualization framework. We identify the main concepts within the current framework and point to their roots to the 1984 work.